4(-x+3)=2(-2x+6)

Simple and best practice solution for 4(-x+3)=2(-2x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-x+3)=2(-2x+6) equation:


4(-x+3)=2(-2x+6)

We simplify the equation to the form, which is simple to understand
4(-x+3)=2(-2x+6)

Reorder the terms in parentheses
+(-4x+12)=2*(-2x+6)

Remove unnecessary parentheses
-4x+12=+2+*(-2x+6+)

Reorder the terms in parentheses
-4x+12=+(-4x+12)

Remove unnecessary parentheses
-4x+12=-4x+12

We move all terms containing x to the left and all other terms to the right.
-4x+4x=+12-12

We simplify left and right side of the equation.
0x=0

0=0

This equation is an identity, so all real numbers are solutions.

See similar equations:

| 4.17n=2.74n-3.29 | | (x+2)(x-1)(3x-6)= | | 42=n+14 | | 2x-7(x-2)=-1 | | 3a+8b-5(9a-2b)= | | 0=0.3x-0.5 | | 2(x+7)-5x=8-5x | | 7x+4(x+9)=4(x+2) | | 250=-16t^2+500 | | 5.77=a+9 | | 4j+j+27=-38 | | 3t-7(t-7)=4(t-4) | | x+y^3=27 | | -3.1=4.75+e | | z-14=82 | | -5.5c+0.56=-1.64 | | 8-7(x+5)=2(x-4) | | 2x-3(x-6)=2(x+3) | | 18n-50n-25n+19n+28n-24=46 | | 3w-3(w-5)=8(w-4) | | 3(2x-5)-4(3x+2)=2-2(x+2) | | 2(x-2)-3x=-12-3x | | 82-b=64 | | (x^2-x+2)(x-5)= | | 6=3-k | | 6x+9(x-3)=5(x-8) | | 82-b= | | 3m-m-m-m+2m=16 | | 4(x+9)=-3(2x-9)+4x | | 22x-10=0 | | 15=19+2(q-18) | | 9x-3(x-2)=2(x-3)+9 |

Equations solver categories